Isolation and screening of fungi from oil palm empty fruit bunch for degradation of lignin in lignocellulolytic components components - Sathiskumar Subramaniam, author; Adibah Yahya, author; Symposium of the Malaysian Socicity for Microbiology (30th: 2008: Pahang) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL